Mechanical properties of steel in aqueous corrosion - Ching Liang, Cho (2010)
Steel is the most common structural material and is used in a wide range of environments. Serious problems from environmental attack may be presented which significantly decrease characteristics of mechanical properties such as tensile, torsion, bending, hardness and fatigue stress and thus durability and service lifetime. In this experiment, the effect of the fresh water environment and sea water environment corrosion to the tensile strength, flexural strength and hardness of AISI 1010 steel will be determined. First, the test specimens will be prepared according to the ASTM standards. Next, the immersion of the steel to the corrosive environment up to a month according to ASTM G31. The specimens were cleaned and tested for tensile flexural and hardness properties. Losses in yield strength and ultimate tensile strength for tensile test, losses in yield load for flexural test and a significant decrease in hardness of the steel is observed after it is corroded compare to the initial condition. The result obtained showed that losses in mechanical properties for specimens exposed to sea water were higher than those exposed to fresh water for every properties tested.